Hakim Konstitusi Adalah Hati dalam Tubuh Mahkamah Konstitusi - Hardianto, Danang (Mahkamah Konstitusi Republik Indonesia, 2014)
Constitutional judges denote a piece of flesh i.e. heart in the body of the Constitutional Court. If it is good, the whole body is good, and if it is bad, or else if it is bad, the whole boy is bad. The good heart is filled by the judges who have impeccable integrity and personality; be fair-minded; and be statesman who have mastered constitution and constitutional law. They therefore have an obligation to make a responsive and prescriptive decision in order to enforce the law based on the morality and the truth. The decision becomes the sun which will continue to shine and illuminate the life of the country.